211 Biosecurity practices associated with antimicrobial usage in farrow-to-finish pig farms. (30th November 2020) - Calderon Diaz, Julia A; O'Neill, Lorcan; da Costa, Maria Rodrigues; Manzanilla, Edgar Garcia
Abstract: The objective of this study was to identify biosecurity practices associated with antimicrobial usage (AMU, mg/live body weight, BW) in pig farms. Biosecurity practices were assessed using the Biocheck.UGentTM questionnaire in 54 Irish farrow-to-finish pig farms. For each farm, information on antimicrobial usage in-feed and water and critically important antimicrobials (CIA) usage was collected. Data were analysed using univariable general linear models in PROC GLM of SAS v9.4. Results are presented as least square means ± SE. In-feed AMU was lower in farms where farm staff wore farm specific clothing and shoes, and washed their hands before entering the stables (55.1±19.12 vs. 159.4±31.49 mg/BW; P=0.007) and it tended (P< 0.10) to be lower in farms where animals were loaded for transport from a centrally located corridor, rather than from separately located corridor (69.5±18.79 vs. 148.4±41.07 mg/BW) and had a maximal density of 0.7 m2/pig in the finisher stage (66.5±29.819.152 vs. 145.1±36.98 mg/BW). Similarly, in water AMU was 14.6 mg/BW lower in farms where farm staff wore farm specific clothing and shoes, and washed their hands before entering the stables and 11 mg/BW lower in farms where carcass storage was regularly cleaned (P< 0.05) compared with farms that did not carry out these practices. Wearing gloves when manipulating carcasses (0.3±0.14 vs. 1.0±0.25 mg/BW having footbaths at the entrance of each building (0.2±0.17 vs. 0.7±0.17 mg/BW), loading animals for transport from a central corridor (0.3±0.13 vs. 1.2±0.28 mg/BW) and a maximal density of 0.7 m2/pig in the finisher stage (0.3±0.13 vs. 1.1±0.25 mg/BW) were associated with lower CIA usage (P< 0.05). The implementation of biosecurity practices was associated with lower AMU. Many of these practices could easily be implemented on farms with relatively low costs. Our results highlight the usefulness of cleaning, disinfections and farm compartmentalization to reduce AMU in pig farms.